The Lifetime of Experiences Questionnaire: Psychometric Properties and Relationships With Memory Function in an Iranian Elderly Sample - Karsazi, Hossein; Hatami, Javad; Rostami, Reza; Moghadamzadeh, Ali (Frontiers in Psychiatry, 2022)
This study aimed to validate the Persian version of the Life Experience Questionnaire (LEQ) and examine the relationship between life experience and memory function. To this end, two studies were conducted. Study one examined the factor structure, internal consistency, and convergent and discriminant validity of the Persian version of LEQ with 247 healthy elderly individuals (M age = 70.17, SD = 4.42; 55.9% women). The exploratory factor analysis yielded a five-factor solution, including Knowledge, Physical, Socialization, Artistic, and Leisure dimensions, which accounted for 42.42% of the explained variance. The internal consistency of the LEQ was in the acceptable range (α = 0.703). Also, the LEQ and its subscales (except the Artistic subscale) had a negative relationship with geriatric depression and a positive relationship with a healthy lifestyle, supporting the measure's convergent and discriminant validity. In the second study, we examined the relationship between LEQ (total and subscales score) and memory function using Pearson correlation and moderating analysis with 149 participants (M age = 70.37, SD = 4.29; 55.03 % women). The results demonstrated that the LEQ total and subscales scores correlated positively with episodic memory. In the same vein, LEQ total score and Knowledge subscale showed a positive correlation with semantic memory. The results of moderation analysis showed that LEQ subscales have a different role in memory decline. The knowledge subscale as a content component moderates the effect of age on semantic memory (B = .005, t = 2.021, p = .045), while the mid-life nonspecific activities, which are based on life stages, moderate the effect of age on episodic memory (B = .007, t = 3.348, p = .001). In conclusion, our results indicated that the Persian version of the LEQ is a valid and reliable instrument for measuring experiences and activities throughout life, which can be used in professional clinical and research settings in the aging context with Iranian elderly samples. Furthermore, our findings suggest that various life experiences can be considered cognitive reserves in old age.